Secreted frizzled-related protein 4 predicts progression of autosomal dominant polycystic kidney disease - Zschiedrich, Stefan; Budde, Klemens; Nürnberger, Jens; Wanner, Christoph; Sommerer, Claudia; Kunzendorf, Ulrich; Banas, Bernhard; Hoerl, Walter H.; Obermüller, Nicholas; Arns, Wolfgang; Pavenstädt, Hermann; Gaedeke, Jens; et al. (Nephrology Dialysis Transplantation, 2015)
Autosomal dominant polycystic kidney disease (ADPKD) is a common autosomal dominant condition associated with renal cysts and development of renal failure. With the availability of potential therapies, one major obstacle remains the lack of readily available parameters that identify patients at risk for disease progression and/or determine the efficacy of therapeutic interventions within short observation periods. Increased total kidney volume (TKV) correlates with disease progression, but it remains unknown how accurate this parameter can predict disease progression at early stages.To identify additional parameters that help to stratify ADPKD patients, we measured secreted frizzled-related protein 4 (sFRP4) serum concentrations at baseline and over the course of 18 months in 429 ADPKD patients.Serum creatinine and sFRP4 as well as TKV increased over time, and were significantly different from baseline values within 1 year.Elevated sFRP4 levels at baseline predicted a more rapid decline of renal function at 2, 3 and 5 years suggesting that sFRP4 serum levels may provide additional information to identify ADPKD patients at risk for rapid disease progression.
EVALuna2:3777